2013
DOI: 10.1517/17460441.2013.761202
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of skin disease for drug discovery

Abstract: Introduction Discovery of novel drugs, treatments, and testing of consumer products in the field of dermatology is a multi-billion dollar business. Due to the distressing nature of many dermatological diseases, and the enormous consumer demand for products to reverse the effects of skin photodamage, aging, and hair loss, this is a very active field. Areas covered In this paper, we will cover the use of animal models that have been reported to recapitulate to a greater or lesser extent the features of human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 175 publications
2
79
0
Order By: Relevance
“…In addition to the recruitment of FADD, the Fas-induced apoptosis pathway can also be mediated by a receptor-interacting protein (RIP), RIP associated ICH/CED-3-homologous protein with a death domain, and procaspase-2 [13]. Fas-mediated apoptosis of keratinocytes has multiple functions and has been implicated in various conditions such as allergic contact dermatitis, wound healing, lupus erythematosus, toxic epidermal necrolysis, and the formation of sunburn cells by UV radiation [14]. Recent studies have demonstrated Fas expression associated with apoptotic keratinocytes in aging human epidermis [15].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the recruitment of FADD, the Fas-induced apoptosis pathway can also be mediated by a receptor-interacting protein (RIP), RIP associated ICH/CED-3-homologous protein with a death domain, and procaspase-2 [13]. Fas-mediated apoptosis of keratinocytes has multiple functions and has been implicated in various conditions such as allergic contact dermatitis, wound healing, lupus erythematosus, toxic epidermal necrolysis, and the formation of sunburn cells by UV radiation [14]. Recent studies have demonstrated Fas expression associated with apoptotic keratinocytes in aging human epidermis [15].…”
Section: Resultsmentioning
confidence: 99%
“…; Avci et al . ). In addition, the vast majority of preclinical studies have been performed using assay conditions ( e.g .…”
Section: Nutraceuticals Purported To Counter the Skin Ageing Processmentioning
confidence: 97%
“…Mitochondria play crucial roles in several age-related diseases, and in the physiology of normal skin aging [37]. The effects of skin photodamage and aging are studied by the use of animal models [38].…”
Section: Role Of Mitochondriamentioning
confidence: 99%
“…Wound healing is studied in a wider range of animal species, and skin infections such as acne and leprosy also have been studied in animal models. Moving to the more consumer-oriented area of dermatology, there are models for studying the harmful effect of sunlight on the skin, and testing of sunscreens, and several different animal models of hair loss or alopecia [38].…”
Section: Age-related Diseases Disorders and Conditions Of The Skinmentioning
confidence: 99%